To what extent does emotional dysregulation account for aggression associated with ADHD symptoms? An experience sampling study. (September 2021) - Murray, Aja; Lavoie, Jennifer; Booth, Tom; Eisner, Manuel; Ribeaud, Denis
Highlights: Aggression strongly co-occurs with ADHD symptoms. It has previously been proposed that emotional dysregulation mediates this link. We tested this using experience sampling over 14 days with 4 assessments per day. Emotional dysregulation was associated with ADHD symptoms. Emotional dysregulation did not mediate their association with aggression. Abstract: Previous research suggests that aggression is associated with ADHD symptoms and this may partly reflect problems with emotional regulation. Using data from the D2M study (n=260) we found that ADHD symptoms were associated with both emotional lability and aggression, but emotional lability did not mediate the ADHD-aggression association. Results suggest that other factors may be more important for explaining elevated levels of aggression in ADHD.